Genome-Wide Analysis in Swine Associates Corneal Graft Rejection with Donor-Recipient Mismatches in Three Novel Histocompatibility Regions and One Locus Homologous to the Mouse H-3 Locus. - Susan Nicholls; Ricardo Pong-Wong; Louisa Mitchard; Ross Harley; Alan Archibald; Andrew Dick; Michael Bailey (PLoS ONE)
In rodents, immune responses to minor histocompatibility antigens are the most important drivers of corneal graft rejection. However, this has not been confirmed in humans or in a large animal model and the genetic loci are poorly characterised, even in mice. The gene sequence data now available for a range of relevant species permits the use of genome-wide association (GWA) techniques to identify minor antigens associated with transplant rejection. We have used this technique in a pre-clinical model of corneal transplantation in semi-inbred NIH minipigs and Babraham swine to search for novel minor histocompatibility loci and to determine whether rodent findings have wider applicability. DNA from a cohort of MHC-matched and MHC-mismatched donors and recipients was analysed for single nucleotide polymorphisms (SNPs). The level of SNP homozygosity for each line was assessed. Genome-wide analysis of the association of SNP disparities with rejection was performed using log-likelihood ratios. Four genomic blocks containing four or more SNPs significantly linked to rejection were identified (on chromosomes 1, 4, 6 and 9), none at the location of the MHC. One block of 36 SNPs spanned a region that exhibits conservation of synteny with the mouse H-3 histocompatibility locus and contains the pig homologue of the mouse Zfp106 gene, which encodes peptide epitopes known to mediate corneal graft rejection. The other three regions are novel minor histocompatibility loci. The results suggest that rejection can be predicted from SNP analysis prior to transplant in this model and that a similar GWA analysis is merited in humans.